Developing and Evaluating the Sustainable Energy Security Index and its Performance in Malaysia - Yusoff, Nora Yusma Mohamed; Bekhet, Hussain Ali (International Journal of Energy Economics and Policy, 2020)
There is an increasing interest in understanding the crucial factors of sustainable development in terms of security of supply, conservation, and environmental impacts. Based on the current energy perspectives, there are serious challenges in achieving energy security and sustainability. Sustainable energy security (SES) must not only consider the security of energy supply-demand in the long-term and short-term, but also emphasise the balance between energy, economy, social, and environmental factors. Based on the five dimensions of energy security (availability, accessibility, affordability, acceptability, and develop-ability), this study aims to develop and evaluate SES index for Malaysia. The weight of energy security indexes was determined using the entropy weight method. Also, the security and rank performance of the five dimensions of energy security and sustainability were calculated using the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method. Then, the five dimensions' scores between 2005 and 2016 were measured. The results reveal that the weight of develop-ability and affordability were the most important weights in Malaysia's SES index system. This implied that the energy supply security greatly influenced the SES of Malaysia. In addition, the highest score in develop-ability reflected the sustainable development capacity of the energy system in low carbon, clean, and optimised mode, which plays a crucial role in Malaysia's energy sustainability. The results also reflected the affordability and ability to resist the negative impact of rising energy prices in Malaysia. Keywords: Energy Security, Sustainability, Performance, Ranking, Weight Entropy Technique, Technique for Order of Preference by Similarity to Ideal Solution Model, Malaysia JEL Classifications: N75, Q41, Q56 DOI: https://doi.org/10.32479/ijeep.8912